Performance and carcass characteristics of broiler chicken fed soybean and sesame/soybean based diets supplemented with or without microbial phytase (2014)
Aims: The experiment was conducted to investigate the performance and carcass characteristics of meat-type chicken fed Soybean Meal (SBM) and Sesame/Soybean Meal (SSBM) supplemented with or without microbial phytase. Study Design: The experiment employed a complete randomized design; all data generated were subjected to analysis of variance, P=0.05. Place and Duration of Study: The study was carried out at the Teaching and Research Farm of the University of Ibadan, Nigeria, between October and December, 2011. Methodology: One hundred and sixty-eight unsexed two weeks old Arbor Acre strain chickens were used in a 35-day feeding trial. Two feeding regimes of soybean meal and Sesame/soybean meal based diets were formulated. Each feeding regime comprised of control diet and two levels of phytase units (300 and 600 FTU/kg) of 500 unit /g activity making a total of six dietary treatments. The birds were fed the experimental diets for a 35- and Feed Conversion Ratio (FCR). At the end of the feeding trial, three birds were slaughtered per replicate to evaluate carcass and meat characteristics. Results: The addition of phytase improved the birds’ performance, FI and FCR. Significant (P<0.05) increase was obtained for apparent retention of nitrogen (67.22%), ash (74.85%), ether extract (65.43%), crude fibre (76.22%) and Phosphorus (45.58%). Cooking loss values increased while the Water Holding Capacity (WHC) reduced with microbial phytase supplementation. Conclusion: Sesame/soybean diet supplemented with 300 FTU/Kg microbial phytase gave optimum performance and should probably be adopted as the feeding regime of choice since it also resulted in better nutrient utilization by the birds.